2020
DOI: 10.1055/s-0040-1713412
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Employee Patient Portal Use and Electronic Health Record Access at an Academic Medical Center

Abstract: Background Patient portals provide patients and their caregivers online access to limited health results. Health care employees with electronic health record (EHR) access may be able to view their health information not available in the patient portal by looking in the EHR. Objective In this study, we examine how employees use the patient portal when they also have access to the tethered EHR. Methods We obtained patient portal and EHR usage logs corresponding to all employees who viewed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…More crucially, previous studies have demonstrated that reaching out may be a sign that a patient or family member uncovered an important safety issue or needed to clarify something important about their care, so this might indicate a sign of increased patient engagement. 10,11 There were several significant limitations in our study. First, the sample size was small with only a 20% response rate in a single institution.…”
Section: Discussionmentioning
confidence: 92%
“…More crucially, previous studies have demonstrated that reaching out may be a sign that a patient or family member uncovered an important safety issue or needed to clarify something important about their care, so this might indicate a sign of increased patient engagement. 10,11 There were several significant limitations in our study. First, the sample size was small with only a 20% response rate in a single institution.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, frequent patient portal users were perhaps more likely to use a greater number of patient portal functions partly because they became familiar with their patient portal, or because they had a higher level of technological or health literacy which allowed them to become proficient patient portal users. [38][39][40][41] Future studies could help ascertain whether technological literacy and patient portal use frequency are associated with increased patient engagement and perhaps better patient selfmanagement.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many expressed keen interest in obtaining more health information and details of their medical records. This demand is persistent among patients across various studies [53][54][55], therefore, promising future success of portal implementation and adoption.…”
Section: Discussionmentioning
confidence: 99%